The Nurse or Midwife at the Crossroads of Caring for Patients With Suicidal and Rigid Religious Ideations in Africa - Aziato, Lydia; Pwavra, Joyce B. P.; Paarima, Yennuten; Konlan, Kennedy Dodam (Frontiers in Psychology, 2021)
Nurses and midwives are the majority of healthcare professionals globally including Africa and they provide care at all levels of the health system including community levels. Nurses and midwives contribute to the care of patients with rigid or dogmatic religious beliefs or those with suicidal ideations. This review paper discusses acute and chronic diseases that have suicidal tendencies such as terminal cancer, diseases with excruciating pain, physical disability, stroke, end-stage renal failure and diabetics who are amputated. It was reiterated that nurses and midwives taking care of these patients should be alert and observant to identify their suicidal tendencies. The paper also discusses religious or spiritual inclinations that negatively affect healthcare access and adherence, especially to biomedical or western medicine. It was emphasized that some religious beliefs do not allow their followers to employ biomedical treatment and nurses and midwives should not impose their faith on patients and their families. The paper ends with a discussion on the specific roles of nurses and midwives in the care of patients with suicidal ideations such as assessment, counselling, administering medication, observation, social interaction, ensuring safety measures and providing an enabling environment for the family to part of the care and for the observation of religious coping strategies. Nurses and midwives should enhance their knowledge and skills on suicide and increase public education on suicide prevention and identification of those at risk.